Development of a screening assay to evaluate the potential of drugs to cause immune-mediated hypersensitivity reactions. (April 2014) - You, Qiang; Cheng, Linling; Li, Dingzhou; Whritenour, Jessica; Kawabata, Thomas T.; Ju, Cynthia
Abstract Evidence suggests that bio-activation of drugs to generate chemically reactive metabolites (RM) that act as haptens to form immunogenic protein conjugates may be an important cause of immune-mediated drug hypersensitivity reactions (IDHR). Although many drugs that form RMs raise concerns about producing IDHR, standard non-clinical testing methods are rarely able to identify compounds with the potential to produce IDHR in humans. The objective of this study was to develop a predictive assay for IDHR that involves: (1) the use of an in vitro drug-metabolizing system to generate the RM that is captured by GSH, (2) conjugating the RM-GSH conjugate to mouse serum albumin (MSA) by using a chemical cross-linker, (3) immunization of mice with RM-GSH-MSA adducts, and (4) ex vivo challenge with RM-GSH-MSA adduct and measurement of lymphocyte proliferation to determine if the RM is immunogenic. The predictivity of the assay was evaluated by using drugs that produce RM and have been strongly, weakly, or not associated with IDHRs in the clinic. While this method requires additional validation with more drugs, the results demonstrate the feasibility of identifying drugs strongly associated with IDHR and the utility of the assay for rank ordering drugs with respect to their potential to cause IDHR.